Edukasi Masyarakat tentang Pelestarian Peninggalan Sejarah dan Cagar Budaya - Wilaela Wilaela; Widiarto Widiarto (MENARA RIAU, 2022)
Many destruction and neglect of historical and cultural heritage are caused by a lack of conservation literacy. The younger generation must be appropriately informed about this issue to build apprehension and give ideas and creativity concerning preservation. Senapelan, as the ancient city area is known now, is rich in historical and cultural value. Unfortunately, the existence of these relics has not been effectively used for the benefit of science and society. On the other hand, a community of observers or historical activists seeking recognition for their efforts in promoting historical heritage and tourism has begun to emerge. Collaboration between universities and historical and tourism observers communities can take place, giving meaning to campus support for conservation efforts carried out by the community. The activity partners are young people who are intended to motivate the community to care for the environment. They get new knowledge, a new and different concept of conservation, and a lasting impact. They can comprehend that conservation is more than just safeguarding cultural heritage or keeping it clean; it is also about developing and exploiting it for the benefit of the community.